Study the Electronic and Spectroscopic Characteristics of p-n Heterojunction Hybrid (Sn10O16/C24O6) via Density Functional Theory (DFT) - Abdulradha, Shaima K.; Hussein, Mohammed T.; Abdulsattar, Mudar Ahmed (Iraqi Journal of Physics, 2023)
The electronic characteristics, including the density of state and bond length, in addition to the spectroscopic properties such as IR spectrum and Raman scattering, as a function of the frequency of Sn10O16, C24O6, and hybrid junction (Sn10O16/C24O6) were studied. The methodology uses DFT for all electron levels with the hybrid function B3-LYP (Becke level, 3-parameters, Lee–Yang-Parr), with 6-311G (p,d)  basis set, and Stuttgart/Dresden (SDD) basis set, using Gaussian 09 theoretical calculations. The geometrical structures were calculated by Gaussian view 05 as a supplementary program. The band gap was calculated and compared to the measured values. The density of state of the hybrid junction (Sn10O16/C24O6) increased because of the increased number of degeneracy states. Theoretical values of bonds for C=C, C=O, and Sn-O are equal to 1.33, 1.20 and 2.27 Å respectively, these bonds values are in good agreement with experimental values of bond length of 1.34 for the C=C bond, 1.23 for the C=O bond, and 2.3 for the Sn-O bond. . The spectroscopic properties, such as IR spectra have shown a peak which is comparable to longitudinal modes of GO and tin dioxide SnO2 at  (1582 and 690) cm-1, respectively.